Watch the view: to enjoy alternative grassroots video - Román, María José (Folios, revista de la Facultad de Comunicaciones y Filología, 2010)
This article presents three youth-led alternative grassroots media collectives working in marginalized areas of the three main colombian cities: the area of Aguablanca, in Cali, Ciudad Bolívar in Bogotá, and north-eastern “comunas” of Medellín. Initially the text characterizes the video-activism fenomena and the social organizations related to it; then it focuses in the colombian cases of study. In the next stage, the article deepens in youth political subjectivity processes related to audiovisual production, and shows the political side of the images created by these youth-led media collectives, rooted in its visual regime, and its non narrative strenght. As a conclusion, the need to awake a more dynamic and active view is highlighted, according to the complexity of the contemporary alternative audiovisual fenomena.